Microbiological assay for gatifloxacin in pharmaceutical formulations - Salgado, HRN; Lopes, CCGO; Lucchesi, MBB (Elsevier B.V., 2006)
A simple, sensitive and specific agar diffusion bioassay for the antibacterial gatifloxacin was developed using a strain of Bacillus subtilis ATCC 9372 as the test organism. Gatifloxacin could be measured in tablets and raw material at concentration ranging 4-16 mu g ml(-1). The calibration graph for gatifloxacin was linear from 4.0 to 16.0 mu g ml(-1). A prospective validation of the method demonstrated that the method was linear (r(2) = 0.9993), precise (R.S.D. = 1.14%) and accurate. The results confirmed its precision and did not differ significantly from others methods described in the literature. The validated method yielded good results in terms of the range, linearity, precision, accuracy, specificity and recovery. We concluded that the microbiological assay is satisfactory for in vitro quantification of the antibacterial activity of gatifloxacin. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: gatifloxacin; fluoroquinolones; microbiological assay; pharmaceutical analysis; quality control; cylinder plate method